On the relative merits of simple and advanced constitutive models in dynamic analysis of tunnels - Kontoe,S; Zdravkovic,L; Potts,DM; Menkiti,CO (Geotechnique, 2011)
This paper compares simple constitutive models that are widely used in engineering practice with more sophisticated methods in the context of a case study. In particular, four constitutive modelling approaches have been considered: a simple elasto-plastic constitutive model (modified Cam-clay), with and without Rayleigh damping; the same model coupled with a cyclic non-linear model that can simulate pre-yield hysteresis; and finally an advanced kinematic hardening model, which is an improved version of the Al-Tabbaa & Wood two-surface model. These four approaches are used to analyse the seismic response of a section of the Bolu tunnels during the 1999 Duzce earthquake. To shed light on the performance of the constitutive models, simple site response finite-element analyses were first undertaken for the studied site, paying particular attention to the calibration of the Rayleigh damping parameters. The results of these analyses, in terms of maximum shear strain, were then used as input to an analytical elastic method (extended Hoeg method) for calculating the thrust and bending moment acting in the tunnel lining. Finally the results of dynamic time domain plane-strain analyses, employing the four adopted constitutive modelling approaches, are compared against field observations and results obtained by the extended Hoeg method, to investigate the ability of the models, of ranging complexity, to mimic soil response under seismic excitation.